The poly(ADP-ribose) polymerase inhibitor niraparib (MK4827) in BRCA mutation carriers and patients with sporadic cancer: a phase 1 dose-escalation trial - Sandhu, Shahneen K; Schelman, William R; Wilding, George; Moreno, Victor; Baird, Richard D; Miranda, Susana; Hylands, Lucy; Riisnaes, Ruth; Forster, Martin; Omlin, Aurelius; Kreischer, Nathan; Thway, Khin; et al. (The lancet oncology, 2013)
Poly(ADP-ribose) polymerase (PARP) is implicated in DNA repair and transcription regulation. Niraparib (MK4827) is an oral potent, selective PARP-1 and PARP-2 inhibitor that induces synthetic lethality in preclinical tumour models with loss of BRCA and PTEN function. We investigated the safety, tolerability, maximum tolerated dose, pharmacokinetic and pharmacodynamic profiles, and preliminary antitumour activity of niraparib. In a phase 1 dose-escalation study, we enrolled patients with advanced solid tumours at one site in the UK and two sites in the USA. Eligible patients were aged at least 18 years; had a life expectancy of at least 12 weeks; had an Eastern Cooperative Oncology Group performance status of 2 or less; had assessable disease; were not suitable to receive any established treatments; had adequate organ function; and had discontinued any previous anticancer treatments at least 4 weeks previously. In part A, cohorts of three to six patients, enriched for BRCA1 and BRCA2 mutation carriers, received niraparib daily at ten escalating doses from 30 mg to 400 mg in a 21-day cycle to establish the maximum tolerated dose. Dose expansion at the maximum tolerated dose was pursued in 15 patients to confirm tolerability. In part B, we further investigated the maximum tolerated dose in patients with sporadic platinum-resistant high-grade serous ovarian cancer and sporadic prostate cancer. We obtained blood, circulating tumour cells, and optional paired tumour biopsies for pharmacokinetic and pharmacodynamic assessments. Toxic effects were assessed by common toxicity criteria and tumour responses ascribed by Response Evaluation Criteria in Solid Tumors (RECIST). Circulating tumour cells and archival tumour tissue in prostate patients were analysed for exploratory putative predictive biomarkers, such as loss of PTEN expression and ETS rearrangements. This trial is registered with ClinicalTrials.gov, NCT00749502. Between Sept 15, 2008, and Jan 14, 2011, we enrolled 100 patients: 60 in part A and 40 in part B. 300 mg/day was established as the maximum tolerated dose. Dose-limiting toxic effects reported in the first cycle were grade 3 fatigue (one patient given 30 mg/day), grade 3 pneumonitis (one given 60 mg/day), and grade 4 thrombocytopenia (two given 400 mg/day). Common treatment-related toxic effects were anaemia (48 patients [48%]), nausea (42 [42%]), fatigue (42 [42%]), thrombocytopenia (35 [35%]), anorexia (26 [26%]), neutropenia (24 [24%]), constipation (23 [23%]), and vomiting (20 [20%]), and were predominantly grade 1 or 2. Pharmacokinetics were dose proportional and the mean terminal elimination half-life was 36·4 h (range 32·8–46·0). Pharmacodynamic analyses confirmed PARP inhibition exceeded 50% at doses greater than 80 mg/day and antitumour activity was documented beyond doses of 60 mg/day. Eight (40% [95% CI 19–64]) of 20 BRCA1 or BRCA2 mutation carriers with ovarian cancer had RECIST partial responses, as did two (50% [7–93]) of four mutation carriers with breast cancer. Antitumour activity was also reported in sporadic high-grade serous ovarian cancer, non-small-cell lung cancer, and prostate cancer. We recorded no correlation between loss of PTEN expression or ETS rearrangements and measures of antitumour activity in patients with prostate cancer. A recommended phase 2 dose of 300 mg/day niraparib is well tolerated. Niraparib should be further assessed in inherited and sporadic cancers with homologous recombination DNA repair defects and to target PARP-mediated transcription in cancer. Merck Sharp and Dohme.